The Concept of Building a Network of Digital Twins to Increase the Efficiency of Complex Telecommunication Systems. (15th March 2021) - Seilov, Sh. Zh.; Kuzbayev, А. T.; Seilov, A. A.; Shyngisov, D. S.; Goikhman, V. Yu.; Levakov, A. K.; Sokolov, N. A.; Zhursinbek, Y. Sh.
Abstract : The technical literature actively discusses ideas for creating digital twins to solve a wide range of problems that arise for enterprises of various kinds. Advances in the areas of information technology and the development of the necessary software really make it possible to obtain important new results through the creation of digital twins. This paper proposes the concept of building a network of digital twins, used to solve a number of actual problems in complex telecommunication systems. Two applications are considered examples of such tasks. The first application is the organization of information feedback for enterprises involved in the life cycle of a telecommunication network: "elaboration of modernization principles, development of equipment, design, construction, and operation." The second application is monitoring traffic, including its atypical behavior, in order to avoid the recurrence of erroneous actions in case of emergency situations. Another important feature of the digital twin network is that it will become an effective tool for conducting interdisciplinary research.